Approaches to state flood recovery funding in Visegrad Group Countries. (26th May 2020) - Slavíková, Lenka; Raška, Pavel; Banasik, Kazimierz; Barta, Marton; Kis, Andras; Kohnová, Silvia; Matczak, Piotr; Szolgay, Ján
ABSTRACT: Flood recovery is an important period in the flood risk management cycle. Recently, flood recovery has become viewed as an opportunity for future flood damage mitigation. Financial flows to cover flood damages and rules regarding their allocation are crucial for supporting or undermining mitigation efforts. In this paper, we map and compare state flood recovery funding in the so-called Visegrad Group Countries (V4), i.e. Czechia, Hungary, Poland and Slovakia, over the past 30 years of their democratic history. We apply a qualitative comparative approach to identify differences and similarities in risk sharing and state flood recovery funding approaches among these countries. Additionally, we reveal how risk sharing is addressed by existing flood recovery funding schemes. The results indicate that national governments have a low willingness to institutionalise ex-ante compensation schemes. Ad hoc instruments initiated shortly after disastrous flooding usually do not provide incentives to reduce future flood damages.